다변량 분석을 이용한 키위 유전자원의 특성 평가 - 이목희(Mockhee Lee); 김홍림(Hong Lim Kim); 이한철(Han-Cheol Rhee); 곽용범(Yong-Bum Kwack); 헤라쓰 무디얀셀라지(H. M. Prathibhani C. Kumariham); 김진국(Jin Gook Kim) (Weon'ye gwahag gi'sulji, 2020)
본 연구는 국내 보존 중인 140여 점의 다래나무속 유전자원 중 주요 재배종인 A. deliciosa 종과 A. chinensis 종의 원예적 특성을 조사·평가하기 위해 수행되었다. 또한, 다변량 분석을 활용해 계통선발에 유용한 형질을 파악하고 형질별로 자원을 분류하여 육종 프로그램의 기초자료로 활용하고자 하였다. 키위프루트 유전자원 28점의 형질을 조사하고 후숙 후 과실 특성을 분석하였다. 키위프루트 유전자원 28점에 대한 형질 조사 결과, 발아기는 3월 하순부터 4월 상순까지였고 만개기는 5월 중하순이었다. 수확기는 10하순부터 11월 중순까지로 만개기보다 길었다. 과중의 범위는 61.3 ‑ 143.2g이었으며 ‘Kuimi’가 평균과중이 143.2g으로 가장 무거웠다. 후숙 후, 가용성 고형물 함량은 ‘Hongyang’이 가장 높았고 비타민 C 함량은 ‘Lushanxiang’이 가장 높았다. 양적 형질 중 과일의 외형에서는 과중이 가장 변이가 높았고 과실 특성에서는 비타민 C 함량, 퀸산 함량, 적정 산 함량 순으로 높은 변이계수를 보였다. 과중은 횡경과 상관계수 r = 0.921의 높은 정의 상관관계를 가졌다. 가용성 고형물 함량은 과중과 r = ‑ 0.154의 약한 부의 상관관계를 보였지만 통계적으로 유의한 차이가 없었다. 주성분분석으로 11가지 양적 형질이 5가지 주성분으로 압축되었으며 5가지 주성분에 기초하여 28개의 키위프루트 유전자원은 4개의 군집으로 나뉘었다. 이 연구의 결과는 키위프루트 유전자원의 특성을 이해하고 육종 프로그램에 있어 교배조합을 선정하는 데 필요한 기초자료가 될 것으로 생각된다. This study was carried out to evaluate the horticultural characteristics of kiwifruit genetic resources (Actinidia spp.) conserved in Korea to identify the useful traits for the selection of a genetic resource, to classify genetic resources by traits, and to use the genetic resources in a breeding program. In the experiment, traits of 28 kiwifruit germplasms were investigated and fruit characteristics after ripening were analyzed. As the results of the characterization of 28 Actinida spp. genetic resources, the bud break period was reported from late March to early April, while the full blooming commenced during mid-May to late May. The harvest date varied from October 20th to November 15th, which was longer than the full bloom date. The kiwifruit weight ranged from 61.3 g to 143.2 g, while ‘Kuimi’ kiwifruit had the highest average fruit weight (143.2 g). The soluble solids content of ripened kiwifruit 30 days after harvest was highest in ‘Hongyang’ (16.8 °Brix) kiwifruit. The highest vitamin C content (165.9 mg/100 g FW) was recorded from ‘Lushanxiang’ kiwifruit. Among the quantitative traits, the fruit weight showed the highest variation in kiwifruit external traits. Among the internal traits of kiwifruit, the coefficient of variation was higher in vitamin C content followed by quinic acid content and titratable acidity. As a result of correlations among the quantitative traits, the kiwifruit weight showed a higher correlation with the fruit diameter than fruit length. The soluble solids content was negatively correlated with kiwifruit weight, but it was not significant. From the principal component analysis, 11 quantitative traits were compressed into 5 components. Based on the 5 components, 28 kiwifruit germplasms were divided into 4 clusters. The results of this study elucidate the characteristics of kiwifruit genetic resources and can be used as a database for selecting cross combination in kiwifruit breeding programs. KCI Citation Count: 3